1998
DOI: 10.1017/s0813483900003077
|View full text |Cite
|
Sign up to set email alerts
|

The Youth Version of the Positive and Negative Affect Schedule: A Psychometric Validation

Abstract: This study investigated the psychometric properties of the revised Positive and Negative Affect Schedule for Children (PANAS-C; Joiner, Catanzaro & Laurent, 1996) in 228 nonclinical children and adolescents aged between 8 and 15 years. The results revealed that the PANAS-C possesses high internal consistency and encouraging convergent validity, as demonstrated by correlations with the theoretically related constructs of Neuroticism and Extraversion. Construct validity was supported through confirmatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Seeing affect as composed of two systems, each one of them categorized as high and low, leads to four different combinations beyond the two-system approach (for a point of view on two-system theories see Keren & Schul, 2009). Wilson, Gullone, and Moss (1998) have shown that there does not exist any significant correlation between the extent of positive and negative affectivity, which implies that a 'divergent validity' appears to be the case. Previous studies (Bood, Archer, & Norlander, 2004;Norlander, Bood, & Archer, 2002;Palomo et al, 2004) have modified and developed the PANAS instrument further through a subject-response based derivation of the four types of affective personalities.…”
Section: Affective Statesmentioning
confidence: 91%
“…Seeing affect as composed of two systems, each one of them categorized as high and low, leads to four different combinations beyond the two-system approach (for a point of view on two-system theories see Keren & Schul, 2009). Wilson, Gullone, and Moss (1998) have shown that there does not exist any significant correlation between the extent of positive and negative affectivity, which implies that a 'divergent validity' appears to be the case. Previous studies (Bood, Archer, & Norlander, 2004;Norlander, Bood, & Archer, 2002;Palomo et al, 2004) have modified and developed the PANAS instrument further through a subject-response based derivation of the four types of affective personalities.…”
Section: Affective Statesmentioning
confidence: 91%
“…Wilson et al 31 indicated that there existed no significant correlations between the PA and NA scales of the Positive Affect and Negative Affect scale (PANAS) under normal conditions. Furthermore, it has been shown, using functional magnetic resonance imaging, that high PA is associated with less mental efforts and greater efficacy in neural processing of working memory in demanding tasks 32 , implying a relationship between affect, cognition and brain functioning 33 .…”
Section: The Notion Of Affective Personalitymentioning
confidence: 99%
“…Other putative neuropathological factors Affective Personality as Cognitive-emotional Presymptom Profiles Regulatory for Self-reported Health Predispositions and characteristics contributing to vulnerability may be associated too with affective state (Watson and Tellegen, 1985); as a consequence, both positive affect (PA) and negative affect (NA) may possess some degree of explanatory value (e.g., Clark and Watson, 1988), despite these scales being correlated with different factors Bood et al, 2004). Although the claim may not always be so (unpublished data), Wilson et al (1998) indicated that there existed no significant correlations between the PA and NA scales of the Positive Affect and Negative Affect scale (PANAS) under normal conditions. Nevertheless, it has been found repeatedly that NA reflects expressions of affect, such as anger, contempt, guilt, shame, fear and depressiveness, that appear to present relatively stable personality characteristics (Watson et al, 1988a,b;Spector and O´Connell, 1994) whereas PA expresses enthusiasm, activity, control and feelings of duty, associated with a positive attitude, both over time and varying circumstance (Watson et al, 1986;McCrae and Costa, 1987).…”
Section: Introductionmentioning
confidence: 98%